Implementasi Program Anti Bullying Di Lingkungan Sekolah SMK Muhamamdiyah 6 Gemolong - Salman Huda Nur Rohimin; Muhammad Syahreza Pahlevi; Alif Andyan (Universitas 45 Surabaya, 2024)
The incidence of student bullying is rapidly increasing across various school levels, necessitating proactive measures and effective responses. This study aims to elucidate the execution of an anti-bullying initiative implemented at SMAN 1 Surakarta. Employing a qualitative methodology with a case study approach conducted at SMAN 1 Surakarta, data was gathered through extensive interviews with key figures and direct observations. Research findings reveal that, in the anticipation and prevention of bullying, SMAN 1 Surakarta enforces an anti-bullying policy through diverse programs, including: (1) the school's active role in preventing and addressing bullying; (2) the adoption of a Child-Friendly School (Sekolah Ramah Anak or SRA) and the appointment of Child-Friendly School Ambassadors; and (3) the provision of human resources training through collaborations with external entities. In conclusion, the anti-bullying program at SMAN 1 Surakarta effectively curtails bullying and underscores the significance of assessing program efficacy to enhance the overall anti-bullying strategy.